Binary contribution to the stopping in fast ion-surface collisions - Gravielle, Maria Silvia (2001)
The mechanism of the binary collision with the free-electron gas in the proximity of a surface is investigated by employing a semiclassical formalism. The surface dynamic screening of the projectile is described with two well-known models commonly used in the literature: the parallel-dispersion (PD) and specular-reflection (SR) models. The Mermin-Lindhard dielectric function is used to represent the dielectric response of the bulk material. The formalism is applied to the calculation of the energy loss by fast protons colliding with an aluminum surface. Results are compared with those obtained with the dielectric formalism, and energy-loss distributions are analyzed. It is concluded that the models used to describe the dynamic screening potential do not seem to give a reliable description of the binary mechanism.